Analyzing the efficacy of subtropical urban forests in offsetting carbon emissions from cities (vol 13, pg 362, 2010) (2011)
Urban forest management and policies have been promoted as a tool to mitigate carbon dioxide (CO2) emissions. This study used existing CO2 reduction measures from subtropical Miami-Dade and Gainesville, USA and modeled carbon storage and sequestration by trees to analyze policies that use urban forests to offset carbon emissions. Field data were analyzed, modeled, and spatially analyzed to compare CO2 sequestered by managing urban forests to equivalent amounts of CO2 emitted in both urban areas. Urban forests in Gainesville have greater tree density, store more carbon and present lower per-tree sequestration rates than Miami-Dade as a result of environmental conditions and urbanization patterns. Areas characterized by natural pine-oak forests, mangroves, and stands of highly invasive trees were most apt at sequestering CO2. Results indicate that urban tree sequestration offsets CO2 emissions and, relative to total city-wide emissions, is moderately effective at 3.4 percent and 1.8 percent in Gainesville and Miami-Dade, respectively. Moreover, converting available non-treed areas into urban forests would not increase overall CO2 emission reductions substantially. Current CO2 sequestration by trees was comparable to implemented CO2 reduction policies. However, long-term objectives, multiple ecosystem services, costs, community needs, and preservation of existing forests should be considered when managing trees for climate change mitigation and other ecosystem services.